Endothelial activation in thromboangiitis obliterans: mechanisms and therapeutic horizons - Wang, Wanting; Chang, Siyao; Zhao, Gang (Frontiers in Immunology, 2025)
Thromboangiitis obliterans (TAO) is a non-atherosclerotic, inflammatory vasculopathy characterized by thrombotic occlusion of small- and medium-sized vessels, leading to tissue ischemia and gangrene. Emerging evidence underscores endothelial cell (EC) activation as a central driver of disease progression, mediated by immune dysregulation, oxidative stress (Nrf2/ROS imbalance), impaired nitric oxide signaling (eNOS/iNOS dysregulation), endoplasmic reticulum and mitochondrial dysfunction, and disrupted copper/iron homeostasis. These pathways collectively promote a prothrombotic, proinflammatory endothelial phenotype, perpetuating vascular injury. Current therapies primarily alleviate symptoms but fail to address underlying EC dysfunction. Recent advances, including stem cell therapy and targeted immunomodulation, offer promising avenues for restoring endothelial homeostasis. However, translating mechanistic insights into durable clinical benefits requires further research into precision medicine approaches and large-scale validation of novel therapeutics. This review summarizes the multifactorial pathogenesis of TAO, emphasizing EC activation as a therapeutic linchpin, and outlines future directions to bridge translational gaps in disease management.